Thyroid psychosis: a case report - A. Izquierdo De La Puente; P. Del Sol Calderón; M. Garcia Moreno (European Psychiatry, 2022)
Introduction We present the case of a patient who after a year of psychotic symptoms is diagnosed with thyroid cancer with hyperthyroidism.